INTRODUCING ”HEALTH” PERSPECTIVE IN OPEN SOURCE WEB-ENGINEERING SOFTWARE PROJECTS, BASED ON PROJECT DATA ANALYSIS - Dindin, Wahyudin; Mustofa, Khabib; Alexander, Schatten; Stefan, Biffl; A Min, Tjoa (2006)
This paper proposes an evaluation process and concept for ”health” indicators that can help getting an overview on a large number of OSS projects. For initial empirical evaluation of the concept, we apply the indicators to well-known OSS projects and discuss the results with OSS experts to investigate the external validity of the indicators